2005
DOI: 10.1002/prot.20623
|View full text |Cite
|
Sign up to set email alerts
|

Compact reduced thioredoxin structure from the thermophilic bacteria Thermus thermophilus

Abstract: The X-ray crystallographic structure of a thioredoxin from Thermus thermophilus was solved to 1.8 A resolution by molecular replacement. The crystals' space group was C2 with cell dimensions of a = 40.91, b = 95.44, c = 56.68 A, beta =91.41 degrees, with two molecules in the asymmetric unit. Unlike the reported thioredoxin structures, the biological unit of T. thermophilus thioredoxin is a dimer both in solution and in the crystal. The fold conforms to the "thioredoxin fold" that is common over a class of nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Calibration of the column with molecular-weight standards showed that these peaks correspond to molecular weights of 12.8, 26 and !70 kDa, respectively. This implied that Trx3 also forms dimers and multimers in solution, as reported for thioredoxins from other species (Rehse et al, 2005;Smeets et al, 2005;Friemann et al, 2003;Weichsel et al, 1996).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Calibration of the column with molecular-weight standards showed that these peaks correspond to molecular weights of 12.8, 26 and !70 kDa, respectively. This implied that Trx3 also forms dimers and multimers in solution, as reported for thioredoxins from other species (Rehse et al, 2005;Smeets et al, 2005;Friemann et al, 2003;Weichsel et al, 1996).…”
Section: Resultssupporting
confidence: 69%
“…Recently, Trx3 has been found to have a functional relationship with GrxR1 (glutathione reductase) and an overlapping function with GSH (Trotter & Grant, 2005). A large variety of thioredoxin structures from various organisms have been determined (Rehse et al, 2005;Smeets et al, 2005;Friemann et al, 2003;Capitani et al, 2000;Weichsel et al, 1996), but the structure of human thioredoxin 2 is that of a mitochondrial Trx. Recently, the crystal structure of Trx2 from the yeast Saccharomyces cerevisiae has also been solved by our group (Bao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The general fold of Trx2 resembles thioredoxins from other sources,16–23 consisting of five mixed β‐strands flanked by four helices [Fig. 1(A)].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the human hTXN1 protein, Phe27 of Trx2 replaces a serine, and its aromatic ring protects Cys34 from the solvent. A phenylalanine is found at the same position in the thioredoxin of the thermophilic bacterium Thermus thermophilus 21…”
Section: Resultsmentioning
confidence: 99%
“…A Trx from the thermophilic bacterium Thermus thermophilus was isolated, and its structure solved to 1.8-Å resolution (83). The folded portion of this Trx is in a more compact form than standard Trxs, although this protein contains, like other Trxs from thermophilic microorganisms, a 30-residue N-terminal extension and a significantly longer C-terminal ␣-helix.…”
Section: Trx/grx From Thermophilic Microorganismsmentioning
confidence: 99%